2022
DOI: 10.20452/pamw.16319
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric manifestations and their attribution to SLE: a retrospective single-center study in the Polish population

Abstract: In this retrospective cross-sectional study, we assessed the prevalence of primary neuropsychiatric systemic lupus erythematosus (NPSLE) using the Italian attribution model in the Polish cohort of patients with SLE. To the best of our knowledge, there are no published studies on the attribution of NP manifestations to primary NPSLE, together with a detailed characterization of disease activity and symptoms in Polish patients. Our study demonstrates that primary NP manifestations occurred mainly in young patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…No significant difference was found in the proportion of all organ involvements in NPSLE and non-NPSLE groups, unlike in Zhang et al ’s study that found a significant difference in the organ involvement 10 and Pawlak-Bus et al’ s study that reported a significantly higher proportion in vasculitis involvement in the NPSLE group. 12 …”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was found in the proportion of all organ involvements in NPSLE and non-NPSLE groups, unlike in Zhang et al ’s study that found a significant difference in the organ involvement 10 and Pawlak-Bus et al’ s study that reported a significantly higher proportion in vasculitis involvement in the NPSLE group. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The greatest clinical value of HCQ was proven by numerous observational studies of SLE populations (Hopkins Lupus Cohort, GLADEL Cohort, Toronto Lupus Cohort). 15 -17 In current clinical practice, HCQ is the primary drug used in most patients with SLE, 70 and it is recommended regardless of the clinical manifestation and disease activity. 18, 71 The HCQ treatment often lasts many years and is continued even during pregnancy and breastfeeding.…”
Section: Anticoagulant Effectmentioning
confidence: 99%
“…Psychotic symptoms including auditory and visual hallucinations occur as a result of psychological symptoms that are present in most diffuse cases and individuals with localised NPSLEs showed a significant frequency of immunological disorders together with cerebral vascular disease [15,16].Generally, approximately one-third of the neuropsychiatry cases were induced directly by SLE. Furthermore, it is still unclear whether the psychiatric manifestations should be considered as a display of CNS lupus or a specific psychological occurrence of mental illness [17][18][19]. Therefore, in this study, we aimed to describe the characteristics of patients presenting with NPSLE in Dr. Sardjito General Hospital between January 2017 to January 2021.…”
Section: Introductionsmentioning
confidence: 99%